Highly sensitive solid chemical sensor for veterinary drugs based on the synergism between hydrogen bonds and low-dimensional polymer networks. Issue 7 (23rd November 2021) - Kuang, Junhua; Yang, Jie; Liu, Kai; Zhao, Zhiyuan; Shi, Wei; Shao, Mingchao; Bian, Yangshuang; Liu, Yanwei; Chen, Jinyang; Qin, Mingcong; Jiang, Lang; Dong, Jichen; et al.
Abstract : To realize the direct and prompt detection of solid veterinary drug additives (VDAs), we prepared a highly sensitive solid sensor based on the synergism between hydrogen bonds and low-dimensional polymer networks to enable a detection limit below 1 ppm. Abstract : The safety of animal-origin foods has a major influence on human health. Although the use of veterinary drug additives (VDAs) significantly promotes the normal growth and development of animals against diseases, the excessive consumption of VDAs is always the most worrying part. Thus, realizing a direct and prompt detection of solid VDAs is highly desirable. In this study, we incorporated a functional unit of triazolo [4, 5- c ] pyridine (TP) in polymer semiconductors. The theoretical simulation demonstrates that TP can effectively form hydrogen bonding with the VDA molecules. Furthermore, highly sensitive polymeric field-effect transistors (PFETs) are fabricated through the configurational design of low-dimensional polymer networks (LDPNs). The conducting channel and hydrogen bonding sites of the LDPN-based PFETs could be directly exposed to the analytes, thereby effectively capturing VDA molecules and converting the stimuli into electrical signals. The obtained PFET-based solid sensors showed highly sensitive and stable detection of melamine powders at a low operation voltage of −5 V. The detection limit realized is lower than the international standards in animal feeds (2.5 ppm). These results demonstrate the promising applications of PFETs for high-efficiency and low-power-consumption sensors for solid detection or biological diagnosis.